Implementation of the SRIKANDI Application in Electronic Records Management at the Regional Inspectorate of East Kalimantan Province, Indonesia - Rahma Wati; M. Aviv Adhitya Putra Pratama; M. Mujiburrahman; Imam Syahid (Manunggal Halim Jaya, 2026)
The advancement of information technology within government agencies has driven the transformation of records management from conventional systems to electronic systems as part of the implementation of the Electronic-Based Government System (Sistem Pemerintahan Berbasis Elektronik—SPBE). A key implementation of this policy is the use of the SRIKANDI application for electronic records management at the Regional Inspectorate of East Kalimantan Province. This study aims to describe the implementation of the SRIKANDI application in managing electronic records and to identify the factors that facilitate and hinder its execution. This research employs a qualitative, descriptive research design. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted using an interactive model comprising data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation. The results indicate that the implementation of the SRIKANDI application has been carried out effectively, supported by adequate infrastructure and internet connectivity. Nevertheless, challenges persist regarding human resource capacity, particularly varying levels of employee proficiency with the application and technical disruptions that affect system stability. Overall, the implementation of the SRIKANDI application has improved administrative order and enhanced the effectiveness of electronic records management within the agency.